PENGUATAN KECERDASAN INTER-INTRAPERSONAL PADA SISWA FASE C MELALUI IMPLEMENTASI KURIKULUM MERDEKA - Albar, Joni; Mardiana, Mardiana (Universitas Islam 45 Bekasi, 2024)
This research uses a descriptive qualitative approach and uses triangulation techniques to collect more accurate data to explain how the free curriculum increases inter and intrapersonal intelligence in phase C students at SD Negeri 27 Kenual. This research involved teachers and students at SD Negeri 27 Kenual. Interviews, observations and documentation were used to collect data. Interviews were conducted to find out teachers' opinions about the implementation of the Merdeka Curriculum and its impact on students' interpersonal and intrapersonal intelligence. Observations are carried out to track student interactions and activities directly during the learning process. Documents consisting of notes and student work results are analyzed to get a better picture. The research results show that the implementation of the Merdeka Curriculum at SD Negeri 27 Kenual has had a positive impact on strengthening students' inter- and intrapersonal intelligence. Teachers have an important role in supporting the development of these two types of intelligence through flexible, interactive and project-based learning approaches. Students show improvements in the ability to interact with classmates and teachers, as well as in self-reflection and self-understanding. The conclusion is that the Merdeka Curriculum can be an effective framework for developing students' inter- and intrapersonal intelligence, as long as it is supported by appropriate learning strategies and active participation from teachers and students